Treatment of infantile-onset Pompe disease in a rat model with muscle-directed AAV gene therapy - Muñoz, Sergio; Bertolin, Joan; Jimenez, Veronica; Jaén, Maria Luisa; Garcia, Miquel; Pujol, Anna; Vilà, Laia; Sacristan, Victor; Barbon, Elena; Ronzitti, Giuseppe; El Andari, Jihad; Tulalamba, Warut; et al. (Molecular metabolism, 2024)
Objective - Pompe disease (PD) is caused by deficiency of the lysosomal enzyme acid α-glucosidase (GAA), leading to progressive glycogen accumulation and severe myopathy with progressive muscle weakness. In the Infantile-Onset PD (IOPD), death generally occurs <1 year of age. There is no cure for IOPD. Mouse models of PD do not completely reproduce human IOPD severity. Our main objective was to generate the first IOPD rat model to assess an innovative muscle-directed adeno-associated viral (AAV) vector-mediated gene therapy. - Methods - PD rats were generated by CRISPR/Cas9 technology. The novel highly myotropic bioengineered capsid AAVMYO3 and an optimized muscle-specific promoter in conjunction with a transcriptional cis-regulatory element were used to achieve robust Gaa expression in the entire muscular system. Several metabolic, molecular, histopathological, and functional parameters were measured. - Results - PD rats showed early-onset widespread glycogen accumulation, hepato- and cardiomegaly, decreased body and tissue weight, severe impaired muscle function and decreased survival, closely resembling human IOPD. Treatment with AAVMYO3-Gaa vectors resulted in widespread expression of Gaa in muscle throughout the body, normalizing glycogen storage pathology, restoring muscle mass and strength, counteracting cardiomegaly and normalizing survival rate. - Conclusions - This gene therapy holds great potential to treat glycogen metabolism alterations in IOPD. Moreover, the AAV-mediated approach may be exploited for other inherited muscle diseases, which also are limited by the inefficient widespread delivery of therapeutic transgenes throughout the muscular system.
Online verfügbar 10 February 2024, Version des Artikels 15 February 2024
Gesehen am 27.09.2024